Startup Ecosystem in the Context of Finland’s Innovation Policy - Rastopchina, Polina (2026)
This bachelor's thesis examines the startup ecosystem of Finland in the context of national innovation policy. The purpose of the study is to analyze how public policy instruments, institutional structures, and financial mechanisms affect the creation, development, and scaling of startups. Finland was chosen as an example because of its high innovation performance, high investment in research and development (R&D), and well-established cooperation between government, academia, and industry. The thesis combines the theoretical foundations of innovation and innovation policy with an empirical analysis of the startup ecosystem in Finland, including key sectors, regional specialization and the business environment. It also evaluates key indicators such as research and development intensity, venture capital activity, and global innovation ratings. The results show that a coordinated and long-term innovation policy plays a crucial role in creating a competitive and dynamic ecosystem of startups. The study also highlights current challenges and future opportunities related to digitalization, sustainable development, and inclusive entrepreneurship.